Correlation of SARS-CoV-2 Neutralizing Antibodies to an Automated Chemiluminescent Serological Immunoassay. (26th December 2020) - Grenache, David G; Ye, Chunyan; Bradfute, Steven B
Abstract: Introduction: Neutralizing antibodies (NAbs) are capable of binding to a virus to render it incapable of infection. The ability of commercially available SARS-CoV-2 serological tests to detect NAbs has not been widely reported. We sought to correlate the antibodies detected by an automated chemiluminescent immunoassay with NAbs. Methods: Residual serum samples from 35 patients that had a positive antibody test using the LIAISON ® SARS-CoV-2 S1/S2 IgG chemiluminescent immunoassay and 2 antibody-negative control sera were tested for NAbs using a plaque reduction neutralization test (PRNT). Results: NAbs were detected in 66% (23/35) of the antibody-positive samples. The immunoassay signal value ranged from 21.7 to 131.3 AU/mL (median, 90.5) with significant correlation between it and the PRNT ( r = 0.61, P = 0.002). In the samples without NAbs, the immunoassay signal ranged from 16.3 to 66.2 AU/mL (median, 27.2). An immunoassay signal cutoff of >41 AU/mL was 91% sensitive and 92% specific for the detection of NAbs. Discussion: It is important that correlates of immunity to SARS-CoV-2 be identified and NAbs are considered to be central indicators of such. PRNT is the gold-standard test for identifying NAbs but it cannot be used for large-scale testing of populations. It is necessary to establish relationships between it and widely used commercial serological assays for SARS-CoV-2.